Phenylpropane biosynthesis and alkaloid metabolism pathways involved in resistance of Amorphophallus spp. against soft rot disease - Gao, Penghua; Qi, Ying; Li, Lifang; Yang, Shaowu; Guo, Jianwei; Liu, Jiani; Wei, Huanyu; Huang, Feiyan; Yu, Lei (Frontiers in Plant Science, 2024)
Soft rot of konjac (Amorphophallus spp.) is a devastating disease caused by the bacterium Pectobacterium carotovorum subsp. carotovorum (Pcc) with serious adverse effects on plantation development, corm quality and crop yield due to the current lack of effective control measures. The main objective of the present study was to elucidate the mechanisms underlying plant resistance to soft rot disease. A combination of transcriptomic and metabolomic analyses demonstrated significant enrichment of differentially expressed genes (DEG) and differentially accumulated metabolites (DAM) associated with plant hormones, phenylpropanoid biosynthesis and, in particular, alkaloid metabolism, in Amorphophallus muelleri following Pcc infection compared with A. konjac, these data implicate alkaloid metabolism as the dominant mechanism underlying disease resistance of A. muelleri. Quantitative real-time polymerase chain reaction analysis further revealed involvement of PAL, CYP73A16, CCOAOMT1, RBOHD and CDPK20 genes in the response of konjac to Pcc. Analysis of the bacteriostatic activities of total alkaloid from A. muelleri validated the assumption that alkaloid metabolism positively regulates disease resistance of konjac.Our collective results provide a foundation for further research on the resistance mechanisms of konjac against soft rot disease.